Upaya Pencegahan Dan Pengurangan Stunting Di Desa Sibalaya Utara - Nursiah Nursiah; Laendatu Paembonan; Mohammad Ega Nugraha (Jurnal Riset dan Inovasi Manajemen, 2023)
North Sibalaya Village is located in Tanambulava district of Sigi regency and is the capital of the district. The stunting rate in the village is fairly high, which is around 36% which is caused by many factors, one of which is malnutrition in pregnant women and children. Therefore, this research was carried out to carry out efforts to prevent and reduce stunting in North Sibalaya Village. The source of data from this study is secondary data, in the form of data obtained from hospitals and posyandu. This type of research is qualitative with descriptive analysis research methods. The methods carried out include deliberation, socialization, posyandu as well as counseling and distribution of PMT. This research was conducted with the aim of being able to find out what efforts are being made to prevent and reduce stunting in the region.